Ca(2+) release via two-pore channel type 2 (TPC2) is required for slow muscle cell myofibrillogenesis and myotomal patterning in intact zebrafish embryos - Kelu, JJ; Webb, SE; Parrington, J; Galione, A; Miller, AL (Elsevier, 2017)
We recently demonstrated a critical role for two-pore channel type 2 (TPC2)-mediated Ca(2+) release during the differentiation of slow (skeletal) muscle cells (SMC) in intact zebrafish embryos, via the introduction of a translational-blocking morpholino antisense oligonucleotide (MO). Here, we extend our study and demonstrate that knockdown of TPC2 with a non-overlapping splice-blocking MO, knockout of TPC2 (via the generation of a tpcn2(dhkz1a) mutant line of zebrafish using CRISPR/Cas9 gene-editing), or the pharmacological inhibition of TPC2 action with bafilomycin A1 or trans-ned-19, also lead to a significant attenuation of SMC differentiation, characterized by a disruption of SMC myofibrillogenesis and gross morphological changes in the trunk musculature. When the morphants were injected with tpcn2-mRNA or were treated with IP3/BM or caffeine (agonists of the inositol 1,4,5-trisphosphate receptor (IP3R) and ryanodine receptor (RyR), respectively), many aspects of myofibrillogenesis and myotomal patterning (and in the case of the pharmacological treatments, the Ca(2+) signals generated in the SMCs), were rescued. STED super-resolution microscopy revealed a close physical relationship between clusters of RyR in the terminal cisternae of the sarcoplasmic reticulum (SR), and TPC2 in lysosomes, with a mean estimated separation of ~52-87nm. Our data therefore add to the increasing body of evidence, which indicate that localized Ca(2+) release via TPC2 might trigger the generation of more global Ca(2+) release from the SR via Ca(2+)-induced Ca(2+) release.